Hak Asasi Manusia Dalam Kerangka Negara Hukum: Catatan Perjuangan di Mahkamah Konstitusi - Andi Muhammad Asrun (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2016)
Abstract: Human rights on the one hand by the concept of natural law is an inherent right of every individual human being since birth, but on the other hand the legality of human rights must be shaped by the flow of positivism. The debate over whether human rights should be stipulated in the constitution also influence the discussion of the UUD 1945. Finally, the UUD 1945 amendments regulate the basic rights of citizens more fully starts from the premise that human rights protection is an important element in the concept of a constitutional state. Incorporated therein also setting mechanism of